UBC®Rapid Test for detection of carcinoma in situ for bladder cancer. Issue 5 (April 2017) - Ecke, Thorsten H; Weiß, Sarah; Stephan, Carsten; Hallmann, Steffen; Barski, Dimitri; Otto, Thomas; Gerullis, Holger
UBC ® Rapid Test is a test that detects fragments of cytokeratins 8 and 18 in urine. We present results of a multicentre study measuring UBC ® Rapid Test in bladder cancer patients and healthy controls with focus on carcinoma in situ (CIS) and high-grade bladder cancer. From our study with N = 452 patients, we made a stratified sub-analysis for carcinoma in situ of the urinary bladder. Clinical urine samples were used from 87 patients with tumours of the urinary bladder (23 carcinoma in situ, 23 non-muscle-invasive low-grade tumours, 21 non-muscle-invasive high-grade tumours and 20 muscle-invasive high-grade tumours) and from 22 healthy controls. The cut-off value was defined at 10.0 µg/L. Urine samples were analysed by the UBC ® Rapid Test point-of-care system (concile Omega 100 POC reader). Pathological levels of UBC Rapid Test in urine are higher in patients with bladder cancer in comparison to the control group (p < 0.001). Sensitivity was calculated at 86.9% for carcinoma in situ, 30.4% for non-muscle-invasive low-grade bladder cancer, 71.4% for nonmuscle-invasive high grade bladder cancer and 60% for muscle-invasive high-grade bladder cancer, and specificity was 90.9%. The area under the curve of the quantitative UBC ® Rapid Test using the optimal threshold obtained by receiveroperated curve analysis was 0.75. Pathological values of UBC ® Rapid Test in urine are higher in patients with high-grade bladder cancer in comparison to low-grade tumours and the healthy control group. UBC ® Rapid Test has potential to be more sensitive and specific urinary protein biomarker for accurate detection of high-grade patients and could be added especially in the diagnostics for carcinoma in situ and non-muscle-invasive high-grade tumours of urinary bladder cancer.